2014
DOI: 10.12691/ajeid-2-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Phylogenetic Analysis of Cystic Echinococcosis Isolated from Camels and Humans in Egypt

Abstract: The objectives of the present study were to investigate strain identification of Echinococcus granulosus infecting camel and human in Qalyubia, Egypt. Therefore partial sequences were generated after gel purification of nested PCR amplified products of mitochondrial NADH 1gene of Echinococcus granulosus complex. Sequences were further examined by sequence analysis and subsequent phylogeny to compare these sequences to those from known strains of E.granulosus circulating globally and retrieved from GenBank. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…E. granulosus s.s. is the most frequent agent of human cystic echinococcosis worldwide: 88% of 1661 genotyped human isolates belonged to this species (Alvarez Rojas et al, 2014). Exceptions are only countries where E. granulosus s.s. is absent or rare in animals in favour of other Echinococcus spp., as is the case in Sudan and Egypt (Khalifa et al, 2014;Omer et al, 2011). Cysts are often fertile in humans, and numerous observations indicate that the high number of cases may be due to increased infectivity (or pathogenicity) of E. granulosus s.s. compared to other Echinococcus species.…”
Section: Echinococcus Granulosus (Sensu Stricto)mentioning
confidence: 86%
“…E. granulosus s.s. is the most frequent agent of human cystic echinococcosis worldwide: 88% of 1661 genotyped human isolates belonged to this species (Alvarez Rojas et al, 2014). Exceptions are only countries where E. granulosus s.s. is absent or rare in animals in favour of other Echinococcus spp., as is the case in Sudan and Egypt (Khalifa et al, 2014;Omer et al, 2011). Cysts are often fertile in humans, and numerous observations indicate that the high number of cases may be due to increased infectivity (or pathogenicity) of E. granulosus s.s. compared to other Echinococcus species.…”
Section: Echinococcus Granulosus (Sensu Stricto)mentioning
confidence: 86%
“…Take into consideration that a few studies used nPCR-ITS1 of rDNA on contrary to NAD1, COX1-mDNA, consequently, a decrease in the number of the reference E. granulosus strains deposited in GenBank (Amer et al, 2015, Khalifa et al, 2014. In the current study, the ITS sequences obtained from human and animals isolates were between 96.9-98.3% homologous to sequences of E. granulosus strains previously detected in Iran, India and Australia.…”
Section: ------------------------------------------------------------mentioning
confidence: 52%
“…In Egypt, except for a few molecular studies have recorded only the presence of the camel strain (G6), equine strain (G4) and buffalo strain (G5) in definite regions and advised to use gene sequencing of ITS1-PCR (Craig et al, 2005). Many studies have shown clearly that we face a predominant sheep strain (G1) with a high percentage (Abd El Baki et al, 2009;Aboelhadid et al, 2013;Khalifa et al, 2014;Taha, 2012). The current study supported the prevalent and dominance of G1 and G6 E. granulosus in most parts of Egypt, especially in rural areas where slaughter is practiced on farms.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Studies illustrated the wide domination of the G6 (camel strain), which favors the role the camel-dog cycle in the transmission of echinococcosis [11,13,30,31]. Here, we have notice that all the collected samples in these studies were originated from the same area (Cairo and Qalubiya provinces), which considered the main localities in Egypt for importing camels and consuming their meats.…”
Section: Discussionmentioning
confidence: 77%